DOMINANTS OF SELF-PRESENTATION OF UKRAINIAN STARTUP FOUNDERS IN LINKEDIN - MYKHAILOVA, M. (Herald of Kyiv Institute of Business and Technology, 2024)
Ukrainian founders of startups as entrepreneurs have the opportunity to independently develop and seek financing, as well as participate in business development programs. In Ukraine, there is a State Fund for the Development of Innovations, which is subordinate to the Ministry of Digital Transformation and works in the areas of grant funding, mentoring, acceleration and coordination (Ministry of Digital Transformation of Ukraine, 2022, December 27). At the same time, startups that cooperated with the Innovation Development Fund not only received support and developed under the coordination of state institutions, but also received publicity through participation in programs, the fund’s website, industry online media, which could increase the number of views of the pages of startups and their founders. The purpose of the study is to find out the peculiarities of self-presentation of Ukrainian startup founders. The main characteristics of startup founders are innovativeness and creativity, specific perception and management of risks, the illusion of control and belief in the law of small numbers, initiative and motivation, as well as the need for achievements, cultural and personal characteristics of a person. Self-presentation of people in social networks occurred through such strategies as the construction of a digital self, the projection of a digital likeness, digital association, or the reorganization of narrative structures, which was determined by the use of social networks for entertainment or relief from boredom, or to achieve social benefit or self-interest. The main characteristic of the self-presentation of Ukrainian startup founders is association with the startup, which is manifested by creating an impression of reliability, portraying the problem and the startup’s product as its solution, the uniqueness of the product, providing additional benefits and customer orientation, as well as by indicating one’s own status or position in the startup and using its logo in images. The main models of self-presentation were the search for clients and self-affirmation, which were described through orientation to collective achievements and interactions with the startup and through orientation to one’s own achievements and interactions with the founder, respectively.